Analisis Nilai Tambah Kelapa pada Agroindustri Virgin Coconut Oil (Studi Kasus Desa Dalang dan Desa Gadung Sari, Kecamatan Selemadeg Timur, Kabupaten Tabanan) - ADNYANI, NI PUTU NILA; AMBARAWATI, IGAA; ARTINI, NI WAYAN PUTU (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.12, No.1, Juli 2023, 2023)
Analysis of Added Value Coconut of Agroindustri Virgin Coconut Oil (Case Study at Dalang Village and Gadung Sari Village, Selemadeg Timur District, Tabanan Regency) Coconut ( Cocos nucifera ) is an important agroindustry commodity for the people of Indonesia. Virgin Coconut Oil is one of the coconut-processed products with high added value. This research aims to (1) Know the added value of coconut into VCO in one production process, (2) Calculate profits received in one year of processing coconut into VCO, and (3) Knowing the obstacles faced by KWT members in VCO business. This research was conducted in Dalang Village and Gadung Sari Village of East Selemadeg Subdistrict, Tabanan Regency of Bali Province from January to February 2021. The types of data collected are qualitative and quantitative data sourced from primary data and secondary data. The collected data is analyzed descriptively quantitatively. The determination of respondents was done through random sampling of 15 KWT (Women's Farmer Group) members in both villages. The variables measured in this study are the added value of coconut into VCO, profits in one year of production and constraints faced. The results showed that KWT members of coconut processors into VCO received an added value of Rp 13,111/kg in one production process. The profit of processing coconut into VCO obtained in 2020 amounted to Rp 6,088,284. The obstacles faced by KWT VCO processors are the limited raw materials of coconut in the rainy season, not having a PIRT license and limited marketing. KWT should buy more coconuts in the dry season to store, create PIRT licenses and expand marketing through local markets and businesses to companies that use VCO.